(untitled) (SCIÉNDO INGENIUM, 2021)
Using the method of genetic algorithms, the synthesis process of a Watt I type six-bar flat mechanism is developed and applied to the design of a polycentric knee prosthesis to guarantee stability in the extension and total flexion phase of the knee during the knee. gait cycle of a person. Six precision points of the trajectory of the instantaneous center of rotation of the coupling link were selected, with a population of one thousand individuals formed with the lengths of links and angles of movement of the mechanism. The fitness function was obtained with the Freudenstein equation applied to two four-bar mechanisms that make up the prosthesis and the design restrictions were: minimum and maximum bar dimensions, Grashof criterion, angular relationships for ternary elements, transmission angle and instantaneous inactive joints.